Pemberdayaan Kesehatan Masyarakat Petani Melalui Pertanian Jagung Hibrida Berbasis Organik di Kecamatan Sungai Betung Bengkayang - Ismail Astar; Agus Suyanto; Setiawan Setiawan; Sri Widarti; Sutikarini Sutikarini; Shinta Rosalina (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Farmer poverty and food insecurity are key social determinants that directly affect community health status. Sungai Betung Sub-district, Bengkayang Regency, has substantial agricultural potential that remains underutilized, resulting in low farmer income, food insecurity, and elevated health risks from chemical pesticide exposure among farmers and their families. This community service program aimed to improve farmer community health through empowerment in organic-based hybrid maize cultivation. Methods included community health education, practical organic farming training (organic fertilizer and Local Microorganism/MOL production), technical field mentoring, and market access facilitation to support income improvement and household food security. The four-month program (March–June 2025) involved 9 students, and the Agricultural Extension Center (BPP). Results demonstrated an average knowledge increase of 51.6% across six measured health domains, enhanced nutritious food production capacity, and established marketing partnerships that support household income improvement. This program affirms that organic-based agricultural empowerment is an effective promotive-preventive strategy for improving rural community health status.